Microstructural characterization and corrosion-resistance behavior of friction stir-welded A390/10 wt% SiC composites-AA2024 Al alloy joints - Aval, Hamed Jamshidi (2024)
This study examined the effect of traverse speed on the mechanical properties, corrosion-resistance behavior, and microstructure of friction stir-welded A390/10 wt% SiC composites AA2024 Al alloy joints. The laminar flow of both materials was found to diminish in the stir zone (SZ) when the traverse speed of the tool increased from 40 to 80 mm/min, lowering their mixing rate. Large aspect ratio Si particles are broken by the tool pin-induced applied plastic strain, which turns them into refined equiaxed particles. Their aspect ratio remains unchanged in the SZ, despite their decreasing size. SiC and Si particles progressively come into view when moving from the AA2024 alloy’s SZ to the composite workpieces. These changes happen abruptly as traverse speed increases due to the lack of an interfacial layer structure. The advancing side (AS)’s SZ grain size drops from 4.2 ± 0.3 μm to 1.2 ± 0.2 μm as the traverse speed drops from 80 to 40 mm/min. Increased traverse speed from 40 to 80 mm/min will result in a 5.8% decrease in elongation percentage (EP) and 8.4%, 36%, and 10.3% increases in the ultimate tensile strength (UTS), corrosion resistance, and yield strength, respectively.